Investigation of Multiply Twins in Mn2.02Co0.98O4 Ceramic by Means of Transmission Electron Microscopy. Issue 10 (24th June 2016) - Ma, Chengjian; Liu, Yunfei; Lyu, Yinong
Abstract : Mn2.02 Co0.98 O4 ceramic with tetragonal spinel structure was prepared by solid‐state coordination reaction method. The phase and microstructure were studied using X‐ray diffractometer (XRD) and transmission electron microscope (TEM), respectively. The results show that the Mn2.02 Co0.98 O4 ceramic exhibits tetragonal spinel structure owing to imperfect quenching. Several kinds of defects were formed in the sample due to the phase transition from cubic spinel at high temperature to tetragonal spinel at room temperature. Two types of 112 twin wall were found in the quenched Mn2.02 Co0.98 O4 ceramic. The presence and the characteristics of twins were investigated. The twins arranged in a cyclic triangle form and the twin boundaries were parallel to (112) plane or ( 1 ¯ 12 ) plane. The possible mechanism for twinning arrangement in the triangle form was proposed according to some crystal geometry model analysis.